FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGUSAHA INDUSTRI RUMAH TANGGA PENGOLAHAN KUE KERING DI KECAMATAN BANJARMASIN UTARA - RISFY NOVENDRI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research isconducted to find out factors of initial capital, labor, raw materials and working hours. Moreover, this research is conducted to find out which factor that simultaneously affects the income, and dominantly influences the income of pastry industry in North Banjarmasin District.This research is using quantitative method in order to obtain initial capital, labor, raw materials and working hours. The data obtained using primary data is a data directly taken from the source. This data is derived from questionnaires and direct interviews with the owner of the pastry industry in the District of North Banjarmasin.Based on the researchit was found that initial capital, labor, raw material, and working hours are the factors that affectthe income of the pastry industry. Subsequently, raw material is the dominant factor that influencing earnings of the pastry industry in District of North Banjarmasin.Keywords : Initial Capital, Labor, Raw Materials, Working Hours, Revenue